Dispersal syndromes drive the formation of biogeographical regions, illustrated by the case of Wallace's Line. Issue 3 (6th January 2021) - White, Alexander E.; Dey, Kushal K.; Stephens, Matthew; Price, Trevor D.
Abstract: Aim: Biogeographical regions (realms) reflect patterns of co‐distributed species (biotas) across space. Their boundaries are set by dispersal barriers and difficulties of establishment in new locations. We extend new methods to assess these two contributions by quantifying the degree to which realms intergrade across geographical space and the contributions of individual species to the delineation of those realms. As our example, we focus on Wallace's Line, the most enigmatic partitioning of the world's faunas, where climate is thought to have little effect and the majority of dispersal barriers are short water gaps. Location: Indo‐Pacific. Time period: Present day. Major taxa studied: Birds and mammals. Methods: Terrestrial bird and mammal assemblages were established in 1‐degree map cells using range maps. Assemblage structure was modelled using latent Dirichlet allocation, a continuous clustering method that simultaneously establishes the likely partitioning of species into biotas and the contribution of biotas to each map cell. Phylogenetic trees were used to assess the contribution of deep historical processes. Spatial segregation between biotas was evaluated across time and space in comparison with numerous hard realm boundaries drawn by various workers. Results: We demonstrate that the strong turnover between biotas coincides with the north‐western extent of the region not connected to the mainland during the Pleistocene, although the Philippines contains mixed contributions. At deeper taxonomic levels, Sulawesi and the Philippines shift to primarily Asian affinities, resulting from transgressions of a few Asian‐derived lineages across the line. The partitioning of biotas sometimes produces fragmented regions that reflect habitat. Differences in partitions between birds and mammals reflect differences in dispersal ability. Main conclusions: Permanent water barriers have selected for a dispersive archipelago fauna, excluded by an incumbent continental fauna on the Sunda shelf. Deep history, such as plate movements, is relatively unimportant in setting boundaries. The analysis implies a temporally dynamic interaction between a species' intrinsic dispersal ability, physiographic barriers, and recent climate change in the genesis of Earth's biotas.